Seizing the Life of Sounds in Contemporary Instrumental Music: Claude Vivier’s (1980), a Spectromorphological Perspective - Mylène Gioffredo (Music & Science)
This essay has been conceived as an invitation into the workshop of the contemporary music analyst. It aims to familiarize scholars who are interested in but unfamiliar with the practices of music analysis by discussing one of our most important challenges: how can we integrate features such as texture, timbre, and space into our analytical discussions? After a brief presentation of an analytical problem concerning Claude Vivier's Zipangu (1980)—the limitations of “traditional” analytical tools that focus on pitch distribution when studying a work emphasizing timbre and texture—and an introduction to some aspects of the music analyst's practice, the first part of this essay (“How to Seize the Life of Sounds?”) presents essential theoretical foundations. On the one hand, it deals with the rationale behind my choices, my rejection of a signal-analysis-based approach (sometimes considered more “objective”), and my adoption of Pierre Schaeffer's ideas and analytical propositions as discussed in his Traité des objets musicaux (1966), as well as the graphical adaptation proposed by Lasse Thoresen in Emergent Musical Forms: Aural Explorations (2015). On the other hand, it summarizes key concepts necessary to fully appreciate the analysis that follows—from Schaeffer's notion of a new solfège and its associated typomorphology to Thoresen's principles of symbolic annotation. In the second part, “Towards a New Conception of Form in Claude Vivier's Zipangu (1980): A Spectromorphological Perspective,” I demonstrate the existence of a (latent) multidimensional space within which the piece operates by applying this analytical framework to several excerpts from Zipangu .